PENGARUH DANA PIHAK KETIGA, FINANCING TO DEPOSIT RATIO, NON PERFORMING FINANCING DAN TINGKAT SUKU BUNGA TERHADAP PENYALURAN PEMBIAYAAN: (Studi Kasus Perbankan Syariah di Indonesia Tahun 2011-2018) - Yulia Yulia; Khofid Ramdani (Fakultas Ekonomi dan Bisnis Islam, 2020)
Introduction: This study aims to determine the effect of third party funds (DPK), financing to deposit ratio (FDR), non performing financing (NPF), and interest rates (BI Rate) on the distribution of financing to Islamic banking in Indonesia for the period 2011-2018.. Research Methods: The sample used in this study is from 10 Islamic bank financial reports in Indonesia. The data used is secondary data in the form of Islamic banking financial ratios. The method of data analysis in this study uses multiple linear regression analysis with the PLS (Pooled Least Square) technique. Results: The results of this study indicate that the variables of Third Party Funds (DPK) and Financing to Deposit Ratio (FDR) have a significant effect on the variable of financing distribution as indicated by a significance value below 0.05, while the Non Performing Financing (NPF) and Interest Rates (BI Rate) variables. does not have a significant effect on the financing distribution variable, which is indicated by a significance value above 0.5. Simultaneously DPK, FDR, NPF and BI Rate have a significant effect on the variable of financing distribution. Conclusion: Third Party Funds (DPK) and Financing to Deposit Ratio (FDR) have a significant effect on the financing distribution variable. Meanwhile, the Non Performing Financing (NPF) and Interest Rate (BI Rate) variable did not have a significant effect on the financing distribution variable. Simultaneously DPK, FDR, NPF and BI Rate have a significant effect on the variable of financing distribution.